PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PENJUALAN KOSMETIK ILEGAL DITINJAU DARI UNDANG-UNDANG NOMOR 17 TAHUN 2023 TENTANG KESEHATAN - Alfina Pulumoduyo; Darmawati, Darmawati; Albert Pede (Fakultas Hukum Universitas Ichsan Gorontalo, 2024)
The objectives of this research are (1) to analyze law enforcement against perpetrators of illegal cosmetic sales in Gorontalo City. (2) To find out the factors that influence law enforcement against perpetrators of illegal cosmetic sales in Gorontalo City. The research method used by researchers is normative legal research or library legal study, namely legal research carried out by examining library materials or secondary data alone. The results of this research show that: (1) Law enforcement against illegal cosmetics dealers by the police is through penal and non- penal measures. The form of penal effort is to arrest the perpetrators of illegal cosmetics dealers and suppliers. Meanwhile, non-penal measures in dealing with the circulation of illegal cosmetics in the jurisdiction of the Gorontalo City Police include conducting raids and providing legal education (2) Factors inhibiting legal enforcement against the circulation of illegal cosmetics, namely; first, lack of coordination between institutions. Second, low public understanding.